Progreso tecnológico, acumulación de capital y crecimiento en América Latina - Juan Alberto Vázquez Mu\~noz; José Fernando Camacho Acevo (Investigación Económica, 2019)
– This paper displays an analysis of the economic growth rates of Argentina, Brazil, Chile and Mexico during the period 1961-2017. Explanations related to total factor productivity and to capital ac- cumulation are here contrasted in a context of growth external constraint. The following conclusiones are reached on empirical grounds: Technological progress is an endogenous variable reacting to variations in aggregate demand necessary to fulfill the dynamic equilibrium of the trade balance; growth rates in those countries are closely linked to the growth rate of their economic capacity; the process of growth acceleration in these economies corresponded to high rates of capital accumulation.
Keywords: F43; O40; O54; 330; Latin America; total factor productivity; capital accumulation; growth external constraint